Guidelines for a weed management that increase the populations of beneficial insects in oil palm (Elaeis guineensis Jacquin). - Mexzón, Ramón (Agronomía Mesoamericana, 2016)
We found that weeds most frequentIy visited by insects were, in descending order, the species of Asteraceae, Euphorbiaceae, Leguminose and Malvaceae. Of those, 23 were annuals and 38 were perennials. The annual plants flowered during the dry season and the perennial during various periods along the year. Most ofthose species grew in fields with young oil palm trees without the "Kudzu" cover, as well as on roadsides, along canal s and drainage and on clearings inside adult plantations. Some perennial plants with extra-floral glands, growing in fields with adult oil palm trees, proved to be very attractive to insects. The increase in the arthropod population (including beneficial insects), can be obtained through a conservative management of the vegetation. We point out the need to support such changes in the vegetation, based on ecological studies, in order to avoid favoring damaging insects and or pathogenic agents, and also in order to evaluate the effect of such measures over health and yield of the crop.